PENGARUH PENAMBAHAN BUAH BIT (Beta vulgaris L.) DAN BUBUK SARI KACANG MERAH (Phaseolus vulgaris L.) PADA PEMBUATAN BOBA - Ermawan, Aniadita Mutia; Fadhilah, Tri Marta (STIKes Mitra Keluarga, 2023)
Introduction: Boba is a drink topping. The target market is teenagers. Teenagers are one of the groups prone to anemia. Anemia is prevented by eating foods containing iron, for example beets and red beans. This research aims to analyze the quality, acceptability and nutritional characteristics. Method: Experimental study design with a 2-factor, Completely Randomized Design with 3 treatment levels. The study was conducted with 40 untrained panelists. Statistical data analysis Friedman test and Wilcoxon test. Result: Sensory, hedonic and ash content analysis results indicated that the F3 treatment was superior. Water content test results received more F1 treatment. The results of the iron test showed that the F2 treatment was better. Conclusion: There are significant differences based on sensory analysis research results. The highest moisture content test results were obtained in F1, the highest ash content test in F3 and the highest iron content test in F2.